2020
DOI: 10.1093/jmcb/mjaa061
|View full text |Cite
|
Sign up to set email alerts
|

RNF219 interacts with CCR4–NOT in regulating stem cell differentiation

Abstract: Regulation of RNA stability plays a crucial role in gene expression control. Deadenylation is the initial rate-limiting step for the majority of RNA decay events. Here, we show that RING finger protein 219 (RNF219) interacts with the CCR4‒NOT deadenylase complex. RNF219‒CCR4‒NOT exhibits deadenylation activity in vitro. RNA-seq analyses identify some of the 2-cell-specific genes and the neuronal genes significantly downregulated upon RNF219 knockdown, while upregulated after depletion of the CCR4‒NOT subunit C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Of note, we observed robust peptide coverage measured for the different CCR4-NOT deadenylase subunits CNOT6, CNOT6L, CNOT7 and CNOT8, suggesting that RNF219 can stably associate with CCR4-NOT complexes containing either subunit. Our finding is consistent with a recent studies, which independently describe the interaction between RNF219 and CCR4-NOT 32 , 33 .
Figure 2 RNF219 binds to the CCR4-NOT complex.
…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Of note, we observed robust peptide coverage measured for the different CCR4-NOT deadenylase subunits CNOT6, CNOT6L, CNOT7 and CNOT8, suggesting that RNF219 can stably associate with CCR4-NOT complexes containing either subunit. Our finding is consistent with a recent studies, which independently describe the interaction between RNF219 and CCR4-NOT 32 , 33 .
Figure 2 RNF219 binds to the CCR4-NOT complex.
…”
Section: Resultssupporting
confidence: 94%
“…We further show that RNF219 inhibits the translation and stabilizes the poly(A) tail of a reporter mRNA. During the course of our study two groups independently reported RNF219 association with human CCR4-NOT, negatively affecting its enzymatic function 32 , 33 . Importantly, loss of the interaction between RNF219 and the CCR4-NOT complex abolishes these two activities.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“… 32 In mouse embryonic stem cells, depletion of CNOT10 was shown to promote the accumulation of specific transcripts. 33 Finally, in trypanosoma, deletion of the CNOT10 orthologue impaired the integrity of the CCR4-NOT complex, and consequently the degradation of many mRNAs. 34 Altogether, the precise organization and functions of the CNOT1 N -CNOT10-CNOT11 module remain enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the interaction region of GGNBP2 comprises approximately 32 amino acids, which form two α-helices that wrap around the HEAT repeats of the C-terminal region of CNOT11 ( Mauxion et al, 2022 ). Because knockdown of CNOT10 in mouse ES cells results in upregulation of a large number of mRNAs ( Du et al, 2020 ), it is tempting to speculate that recruitment of Ccr4-Not via the N-terminal module can serve as a mechanism for the regulation of mRNA levels ( Mauxion et al, 2022 ).…”
Section: Regulation Of Mrna Deadenylation By Sequence Elements In 3’ Utrmentioning
confidence: 99%